Simulation of advanced aircraft and evaluation of its flight dynamic characteristics - Yu, Lu. (2010)
Simulation of flight dynamics is a very important and crucial component of any large aircraft program. Simulation is meant to replicate the real-life environment and the behaviour of an aircraft in flight. Comparing with experiment-based simulation of the aircrafts, computing programming based simulation is more efficient and cost-saving, especially with the rapid development of computing technology. In this project, a simulated model of a UAV is built in a PC-based environment.